Invigorating care farm ecosystem based on public service innovation: Case of South Korea - Hodong Lee; Bo-Young Kim (Administrative Sciences, 2022)
Recently, the importance of care farming has been emphasized worldwide for the purpose of public health and healing, and, in particular, discussions on innovative transformation and expansion of the care farm ecosystem have continued in terms of convergence of agriculture and welfare. This study aims to present influencing factors based on a hierarchical concept framework for revitalizing care farm ecosystem based on public service innovation. To this end, the AHP methodology was used. Through previous studies, 16 variables were derived within four categories: recognition, structure, leadership, process, and recognition of variables that affect the activation of the care farm ecosystem and conceptualized them through Delphi techniques. In addition, a survey was conducted on 28 stakeholders in care farming to derive the importance of each variable. As a result of the analysis, 'reliability' was derived as the most important factor, followed by factors such as human competence, vision, civic participation, and innovation awareness. Hence, it was confirmed that trust and communication between stakeholders are important to lead the innovative public service ecosystem of care farm, and above all, human competence is an important influencing factor.
Keywords: 350; care farm; ecosystem; public service; innovative service; analytic hierarchy process